Perceived organizational support and procedural justice towards job performance of higher education institute - Djungjunan, Djembar; Pawirosumarto, Suharno; Yazid, Mohd Faizun Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this paper are to investigate the relationship between the perceived organizational support and procedural justice towards the job performance. Both predictors are equally important and have been measured in past research but related to many other industry and country background. This study is about the universities in Indonesia. 200 respondents were involved in this data collection exercise. Questionnaire was distributed through email direct to the target respondent. List of respondents obtained from the head of faculty from selected universities. The results indicate that only perceived organizational support influence towards job performance while the procedural justice is not significant. Further study is needed in order to explore further on how the procedural justice was implement at the university level. Universities should take into action the findings of this results as it may affect the overall job performance among the employee of universities.